Olfm4 Is Highly Expressed in HCC Patients and as a Biomarker and Therapeutic Target for HCC - Yulong Wei; Qingzhu Song; Fenglan Zhang; Tian Yuan (Canadian Journal of Gastroenterology and Hepatology)
Hepatocellular carcinoma (HCC) is one of the primary types of cancer that claims many lives worldwide, and its incidence continues to increase. Conventional therapies against liver cancer are inadequate, and the pathogenesis of HCC remains unclear. Thus, not only are more effective therapies to treat HCC required but also identification of the key genes involved in its pathogenesis is important for developing such therapies. This study found that olfactomedin 4 (OLFM4) level is higher in HCC patients than in healthy individuals. Furthermore, HCC patients also have higher messenger ribonucleic acid (mRNA) expression level in HCC tissues than in liver paracancerous tissues. OLFM4 has high predictive capacity as a biomarker for HCC and closely correlates to tumor size. It is confirmed that OLFM4 contributes to cancer cell proliferation, and HIF1α is involved in this process. Thus, the OLFM4/HIF-1α axis might be a target signaling pathway for developing novel drugs to treat HCC.